Mapping the Social Media Behavior of Serbian Adolescents: Usage Patterns, Affective Experiences, and Communication Preferences - Mojović Zdravković, Kristina; Krstić, Ksenija (Psihološka istraživanja, 2025)
This study examines the dynamics of social media usage among adolescents in Serbia, focusing on their usage habits, affective experiences and communication preferences. The data were obtained by online surveying 391 adolescents (63.9% girls; Mage = 16.09, SD = 1.36) in the beginning of 2023. Through questionnaire data analysis and qualitative content analysis, it explores adolescents' engagement with various social media platforms, highlighting Instagram as the predominant choice. Examining the nuanced perspectives on online versus face-to-face communication, the study reveals that while online communication offers practicality and efficiency, face-to-face interaction is valued for its emotional depth and transparency. The results of the questionnaire on the frequency and activities of using SNSs and the accompanying affective experiences indicate that among adolescents from our sample, we can distinguish three groups of SNS users: "SNS Balancers", "SNS Enthusiasts" and "SNS Ambivalents." Each cluster exhibits unique patterns of SNS usage and affective experiences, highlighting the diverse ways in which adolescents interact with online platforms. The research underscores the need for nuanced longitudinal investigations into adolescent online behavior, suggesting potential avenues for future exploration.
Keywords: Social Network Sites; Online Communication; Face-to-face Communication; Affective Experiences on Social Network Sites; Adolescents